Fibrous Mini-Collagens in Hydra Nematocysts - Holstein, Thomas W. (Science, 1994)
Nematocysts (cnidocysts) are exocytotic organelles found in all cnidarians. Here, atomic force microscopy and field emission scanning electron microscopy reveal the structure of the nematocyst capsule wall. The outer wall consists of globular proteins of unknown function. The inner wall consists of bundles of collagen-like fibrils having a spacing of 50 to 100 nanometers and cross-striations at intervals of 32 nanometers. The fibrils consist of polymers of "mini-collagens," which are abundant in the nematocysts of Hydra. The distinct pattern of mini-collagen fibers in the inner wall can provide the tensile strength necessary to withstand the high osmotic pressure (15 megapascals) in the capsules.